Synthesis and characterization of magnetoliposomes containing nickel ferrite nanoparticles covered with gold for applications in phototherapy - Rio, Irina Soraia Rainho (2020)
In this work, nanoparticles with magnetic/plasmonic properties of nickel ferrite decorated with gold nanoparticles and core/shell nickel ferrite/gold nanoparticles were prepared and characterized. The synthesized nanoparticles were used for the preparation of solid magnetoliposomes (SMLs), these systems being our target of study. The nanosystems were evaluated for the ability to cause local heating upon excitation in the gold plasmonic band. For that, fluorescence quenching of rhodamine B incorporated in SMLs lipid layer was measured. The developed multifunctional nanosystems have shown promising results for application in combined cancer therapy (chemo/phototherapy).